In vitro exposure of human lens epithelial cells to X-rays at varied dose-rates leads to protein-level changes relevant to cataractogenesis. (3rd June 2021) - Chauhan, Vinita; Vuong, Ngoc Q.; Bahia, Simran; Nazemof, Nazila; Kumarathasan, Premkumari
Abstract: Background: Accumulated body of evidence shows that ionizing radiation increases the risk of cataracts. The mechanisms are not clear and the International Commission on Radiological Protection indicates a need for research into understanding the process, particularly at low doses and low dose rates of exposure. Purpose: This study was designed to examine protein-level modifications in a human lens epithelial (HLE) cell-line following radiation exposures. Materials and methods: HLE cell-line was subjected to X-irradiation at varied doses (0-5 Gy) and dose-rates (1.62 cGy/min and 38.2 cGy/min). Cells were collected 20 h post-exposure, lysed and proteins were clarified following fractionation by a molecular weight cut-off filtration method. Fractionated cellular proteins were enzymatically digested and subjected to mass spectrometry analysis. Results: Statistically significant radiation dose-related protein changes compared to the control group were identified. Heatmap and hierarchical clustering analysis showed dose-rate dependant responses. Pathway analysis mapped the proteins to biological functions of mitochondrial dysfunction, reactive oxygen species generation, cell death, cancer, organismal injury and amyloidosis. Conclusion: Overall findings suggest that ionizing radiation exposure of HLE cells by mediating dose rate-dependant oxidative stress and cell death-related mechanisms, can be relevant to cataractogenesis.